Deviation from Dynamic and Personalized Optimal Blood Pressure Targets is Associated With Worse Functional Outcomes After Aneurysmal Subarachnoid Hemorrhage. (1st September 2019) - Silverman, Andrew; Kodali, Sreeja; Strander, Sumita; Gilmore, Emily; Kimmel, Alexandra; Wang, Anson; Cord, Branden J; Falcone, Guido; Hebert, Ryan Matthew; Matouk, Charles C; Sheth, Kevin; Petersen, Nils
Abstract: INTRODUCTION: Effective blood pressure (BP) management after aneurysmal subarachnoid hemorrhage (aSAH) is critical for maintaining optimal cerebral perfusion and protecting the brain from further injury. How to best manage BP during the early stages of aSAH remains uncertain. In this study, we calculated individualized BP thresholds at which cerebral autoregulation was best preserved. We analyzed how deviating from these limits correlates with functional outcome. METHODS: We prospectively enrolled 31 patients with aSAH. Autoregulatory function was continuously measured by interrogating changes in near-infrared spectroscopy (NIRS)-derived tissue oxygenation – a surrogate for cerebral blood flow – as well as intracranial pressure (ICP) in response to changes in mean arterial pressure (MAP) using time-correlation analysis. The resulting autoregulatory indices were used to trend BP ranges at which autoregulation was most preserved. The percent time that MAP exceeded limits of autoregulation (LA) was calculated for each patient. Functional outcome was assessed using the modified Rankin Scale (mRS) at discharge and 90 d. Associations with outcome were analyzed using ordinal multivariate logistic regression. RESULTS: Personalized LA were computed in all patients (age 57.5, 23F, mean WFNS 2, monitoring time 67.8 h). Optimal BP and LA were calculated on average for 89.5% of the total monitoring period. ICP- and NIRS-derived optimal pressures and LA strongly correlated with one another ( P < .0001). Percent time that MAP deviated from LA significantly associated with worse functional outcome at discharge (NIRS P = .001, ICP P = .004) and 90 d (NIRS P = .002, ICP P = .003), adjusting separately for age, WFNS, vasospasm, or delayed cerebral ischemia. CONCLUSION: Both invasive (ICP) and non-invasive (NIRS) determination of personalized BP thresholds for aSAH patients is feasible, and these 2 approaches revealed significant collinearity. Exceeding individualized autoregulatory thresholds may increase the risk of poor functional outcomes.